Pengaruh Pemahaman Perpajakan, Penerapan E-Filling, Tarif Pajak, Dan Ketegasan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM Dengan Kesadaran Wajib Pajak Sebagai Variabel Moderasi Di Kabupaten Nganjuk - Randi, Muhammad; Linawati; Nurdiwaty , Diah (Business and Investment Review, 2024)
The premise of this study is that tax revenue serves as a source of money for the Indonesian government, and in order to increase state tax revenue, the MSME sector must be strengthened. The government must consider additional elements that may affect tax compliance in addition to establishing tax rules targeted at boosting tax compliance. This research aims to determine the effect of understanding taxation, the application of e-filling, tax rates, and the strictness of tax sanctions on MSME taxpayer compliance with taxpayer awareness as a moderating variable in Nganjuk Regency. This study employs a causal quantitative approach as its methodology. 2,322 MSMEs registered with the Nganjuk Regency Cooperatives and Micro Enterprises Service comprised the study's population. Determining the sample using the purposive random sampling method and using the Slovin formula was 71 samples. The data used in this research uses primary and secondary data. The research instrument uses a questionnaire with a Likert scale. This research uses multiple linear analysis with MRA. The research's findings indicate that while tax rates and the severity of tax penalties have a considerable impact on taxpayer compliance, knowing taxation and e-filling implementation do not. Then, while the implementation of e-filling and tax sanctions is not regulated by taxpayer knowledge, taxpayer awareness moderates understanding and rates.